Detrital zircons from late Paleozoic accretionary complexes in north-central Chile (28°-32°S): Possible fingerprints of the Chilenia terrane - Álvarez, J. (2011)
During the Paleozoic the Andean basement of central Chile and Argentina grew westwards by the amalgamation of diverse tectonostratigraphic terranes some of them derived from Laurentia. The last to be accreted, in the Devonian, corresponds to the hypothetical Chilenia terrane. However, direct evidences about the nature of its basement are scarce because volcanics and intrusives associated to a Late Paleozoic arc and the Choiyoi Large Igneous Province concealed almost all older geological units. Indirect evidences about the nature of Chilenia can be obtained from the examination of the detrital zircon age populations in late Paleozoic accretionary prisms formed after its collision along the Pacific margin of Gondwana which may have incorporated sediments derived from the erosion of the Chilenia basement. Zircon populations from three of these accretionary complexes, El Tránsito, Huasco and Choapa (north-central Chile, 28-32°S) include Ordovician (Famatinian), Cambrian (Pampean), Neoproterozoic (Brasiliano) and Mesoproterozoic (Grenvillian) zircons whose sources can be tracked to Gondwana. Nevertheless, the three complexes also include a very large subpopulation of zircons that cannot easily be traced to well-known Gondwana sources and that are derived from the erosion of late Neoproterozoic to Early Cambrian (580-530 Ma) magmatic/metamorphic sources, that possibly form a significant component of the Chilenia microcontinental basement.